Effects of Germinated Lentil Flour on Dough Rheological Behavior and Bread Quality - Denisa Atudorei; Silvia Mironeasa; Georgiana Gabriela Codină (Foods, 2022)
The present study analyzed the effects of germinated lentil flour (LGF) addition at different levels in wheat flour (2.5%, 5%, 7.5%, and 10%), on dough rheological behavior, dough microstructure, and bread quality. Creep-recovery tests showed that the dough samples with high levels of LGF addition presented a higher resistance to flow deformability of the dough. Dough microstructure as analyzed using EFLM showed an increase in the protein area (red color) and a decrease in the starch (green color) amount with the increased level of LGF addition in the wheat flour. It was found that the LGF addition led to the improvement of the porosity, specific volume, and elasticity of the bread samples. The breads with LGF addition were darker and had a slightly reddish and yellowish tint. The bread textural parameters highlighted significant (p < 0.05) higher values for firmness and gumminess and significant (p < 0.05) lower ones for cohesiveness and resilience for the bread with LGF addition when compared with the control. The bread samples with a 2.5% and 5% addition had a more dense structure of the crumb pores. Regarding sensory evaluation, the bread samples with LGF addition in the wheat flour were well appreciated by the consumers. The addition also was desirable due to the fact that it supplemented bread with a greater amount of protein and minerals due to the composition of lentil grains. Therefore, LGF could be successfully used as an ingredient for bread making in order to obtain bread with an improved quality.